Specific detection of Lysobacter antibioticus strains in agricultural soil using PCR and real-time PCR. Issue 20 (10th September 2018) - Lina, Fu; Ting, Wang; Lanfang, Wei; Jun, Yang; Qi, Liu; Yating, Wang; Xing, Wang; Guanghai, Ji
Abstract: Lysobacter antibioticus is an important biocontrol bacteria against phytopathogens in soil, and with the ability to produce nonvolatile antimicrobial metabolites has been extensively characterised. It is important to establish applicable techniques to detect and monitor L. antibioticus directly and accurately in soil samples. We developed and tested 13 primer sets according to phenazine gene ( phzA, phzB, phzD, phzF, phzS ) and the cyclohexanone monooxygenase gene ( phzNO1 ); a pair of primer phzNO1 F1/phzNO1 R1 based on the cyclohexanone monooxygenase ( phzNO1 ) gene of L. antibioticus strain OH13 was selected and optimized polymerase chain reaction (PCR) amplification conditions for rapid and accurate detection. After screening eight strains of L. antibioticus, two strains of Lysobacter enzymogenes, one strain of Lysobacter capsici, Arthrobacterium, Bacillus, Microbacterium, Burkholderia, Pseudomonas and other bacterial strains isolated from different agricultural soils, the phzNO1 F1/phzNO1 R1 primers amplified a single PCR band of about 229 bp from L. antibioticus . The detection sensitivity with primers phzNO1 F1/phzNO1 R1 was 5.14 × 10 4 fg/25μL of genomic DNA and 2.254 × 10 10 to 2.254 × 10 11 colony-forming units/mL for the soil samples. Quantitative PCR assays were to develope as a specific method to monitor the L. antibioticus population in soil as well as guide soil micro-ecological management. Abstract : Specific detection of Lysobacter antibioticus strains.